(3dGejI GdYLes - (3GdWZQGFj GdCUHgGfj, CHh ESeGYjd, eDjO GdOjf, GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, (B513 (3g`s
(3ChdgG (B:s
(3hHYO aEf GdbUjOI GdehSheI HdGejI GdYLe QMe Gddg fGXe YbOgG hQGbe HQOgG bGd GdWZQGFj(B: (3CUGdI GdQCj UGfJfj Yf GdNWd (B*** (3hMdjI GdaVd RGfJfj dOi GdYWds
(3BNQgG (B:s
(3heG CJi HGdhGh aj UOZg (B*** (3EdG hbO QJH aj YWag , hda aj GdHQOI CYWGag (B*** (3MJi jWjH GdfTQ ef dags
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 246s
(3eYLe GdeDdajf(B: 1 / 628s
(3cTa GdXfhf(B: 2 / 1537s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs